Sigma Male Portrayal in Fight Club Movie: Roland Barthes Semiotic Analysis - Trisulo, Disha Affya; Andriano, Stefanus (Communicare : Journal of Communication Studies, 2024)
Sigma Male ideology, a 'picture-perfect' hegemonic masculinity portrayal that has been criticized for promoting toxic masculinity and misogyny despite its rise in popularity. Sigma Male ideologists tend to find representations in media, and one of them being the movie Fight Club. Fight Club, a movie produced by David Fincher on 1999 talks about Jack (Narrator), a white-collar worker who found his corporate and consumerist lifestyle suffocating and had his life turn upside down after engaging a friendship with a charismatic and carefree man, Tyler Durden. Using Roland Barthes' semiotic theory, this research analyzed meanings and symbols of the scenes that portrayed the characteristics of Sigma Male. With a method of qualitative descriptive, 14 scenes were analyzed throughout the movie. Through this research, the result that can be concluded would be the Sigma Male characteristics portrayed in the movie, which is nihilism, detachment from women, and non-conformity.